(untitled) (Web of Technology: Multidimensional Research Journal, 2023)
At the present time, human society is facing a number of global challenges that pose a serious threat to the future destiny of humanity. In our opinion, the environmental problem is one of the most dangerous threats. An environmental threat is a violation of the natural conditions necessary for human life. The environmental problem in Central Asia is primarily the Aral Sea problem. The drying up of the Aral Sea is one of the issues in the focus of Uzbekistan and the world community. This article provides information on the above processes and discusses important factors in improving the efficiency of water resources and their use.